Prevalence, Characteristics, and Management of Chronic Noncancer Pain Among People Who Use Drugs: A Cross-Sectional Study. Issue 11 (31st August 2020) - Kaboré, Jean-Luc; Dassieu, Lise; Roy, Élise; Jutras-Aswad, Didier; Bruneau, Julie; Pagé, M Gabrielle; Choinière, Manon
Abstract: Introduction: Most studies on chronic noncancer pain (CNCP) in people who use drugs (PWUD) are restricted to people attending substance use disorder treatment programs. This study assessed the prevalence of CNCP in a community-based sample of PWUD, identified factors associated with pain, and documented strategies used for pain relief. Methods: This was a cross-sectional study nested in an ongoing cohort of PWUD in Montreal, Canada. Questionnaires were administered to PWUD seen between February 2017 and January 2018. CNCP was defined as pain lasting three or more months and not associated with cancer. Results: A total of 417 PWUD were included (mean age = 44.6 ± 10.6 years, 84% men). The prevalence of CNCP was 44.8%, and the median pain duration (interquartile range) was 12 (5–18) years. The presence of CNCP was associated with older age (>45 years old; odds ratio [OR] = 1.8, 95% CI = 1.2–2.7), male sex (OR = 2.3, 95% CI = 1.2–4.2), poor health condition (OR = 1.9, 95% CI = 1.3–3.0), moderate to severe psychological distress (OR = 2.9, 95% CI = 1.8–4.7), and less frequent cocaine use (OR = 0.5, 95% CI = 0.3–0.9). Among CNCP participants, 20.3% used pain medication from other people, whereas 22.5% used alcohol, cannabis, or illicit drugs to relieve pain. Among those who asked for pain medication (N = 24), 29.2% faced a refusal from the doctor. Conclusions: CNCP was common among PWUD, and a good proportion of them used substances other than prescribed pain medication to relieve pain. Close collaboration of pain and addiction specialists as well as better pain assessment and access to nonpharmacological treatments could improve pain management in PWUD.